Eliciting Illegal migration rates through list randomization - David McKenzie; Melissa Siegel (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
Most migration surveys do not ask about the legal status of migrants due to concerns about the sensitivity of this question. List randomization is a technique that has been used in a number of other social science applications to elicit sensitive information. We trial this technique by adding it to surveys conducted in Ethiopia, Mexico, Morocco and the Philippines. We show how, in principal, this can be used to both give an estimate of the overall rate of illegal migration in the population being surveyed, as well as to determine illegal migration rates for subgroups such as more or less educated households. Our results suggest that there is some useful information in this method: we find higher rates of illegal migration in countries where illegal migration is thought to be more prevalent and households who say they have a migrant are more likely to report having an illegal migrant. Nevertheless, some of our other findings also suggest some possible inconsistencies or noise in the conclusions obtained using this method, so we suggest directions for future attempts to implement this approach in migration surveys.
Keywords: F22; C83; J61; K42; 330; Illegal migration; List Randomization; Item Count Method; Survey Techniques